Improving IT Service Management (ITSM) Capability in Small Application Development Firms Using FitSM: A Case Study Integrated with Socio-Technical Systems Theory - Kristiani, Evelline; Marcel, Marcel (Journal of Information Systems and Informatics, 2024)
This paper looks at how the FitSM framework, together with Socio-Technical Systems (STS) theory, can help improve IT Service Management (ITSM) in a small software development firm. Limited resources often cause small businesses to manage services inefficiently, which leads to inconsistent delivery and dissatisfaction among clients. The study focuses on a single software company in Jakarta, where ITSM processes like incident management, change management, and configuration management were assessed. The research involved interviews with key staff, an evaluation of current practices, and a gap analysis to identify areas needing improvement. The results show that most processes are at an early stage, with some progress in Configuration Management. By using FitSM’s structured approach and addressing teamwork and communication issues through STS theory, the company can improve service reliability and efficiency. The study concludes that combining FitSM with socio-technical principles provides a practical solution for small companies to enhance their ITSM practices and overall service quality.
Keywords: it service management; fitsm; socio-technical system; capability level; process improvement